The Effect of Current Ratio, Price to Book Value, and Debt to Equity Ratio on Return on Assets (in Food and Beverage Companies Listed on the Indonesia Stock Exchange in 2021-2023) - Dera, Annisa; Sutrisno; Febrianti, Reni (Universitas Mohammad Husni Thamrin, 2025)
The food and beverage industry is a strategic sector that makes a significant contribution to the national economy. This growth is inseparable from the increasing population, increasingly widespread urbanization, and changes in people's lifestyles, which tend to prefer ready-to-eat food and practical drinks. Furthermore, the development of digital technology, particularly e-commerce and food delivery services, has opened up significant opportunities for companies to reach a wider market without geographical limitations. This study aims to determine the effect of the Current Ratio, Price to Book Value, and Debt to Equity Ratio on Return on Assets (in Food and Beverage Companies Listed on the Indonesia Stock Exchange in 2021-2023). The method used is quantitative descriptive analysis. The data used is secondary data in the form of annual financial reports obtained from the official website of the Indonesia Stock Exchange. The analytical technique used is multiple linear regression analysis to test the effect of each independent variable on the dependent variable. The results of the study show that partially, Current Ratio does not have a significant effect on ROA, Price to Book Value does not have a significant effect on ROA, Debt to Equity Ratio has a negative and significant effect on ROA. These findings provide implications for investors and management of Food and Beverage companies in considering the company's financial structure and operational efficiency in increasing profitability.